The Influence of Celebrity Endorsers, Brand Image, and Quality of Service on Buying Decisions through Consumer Trust in Digital Video Streaming Service: A Case Study of Disney+ Hotstar - Alya Chantika; Rosmalina; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The purpose of this study is to investigate the correlation between celebrity endorsers, brand image, quality of service, and consumer trust, and how they impact consumer buying decisions. The data for this research was collected via a GoogleForm questionnaire, and was shared through social media. The study was conducted over a period of one month, from October 19 to November 2, 2023. The research population consists of people residing in Jabodetabek who have used Disney's digital video streaming services for at least a month. The research methodology uses quantitative analysis with the Fornell-Larcker criterion, goodness of fit R-square, and hypothesis testing based on T statistics. The Smart PLS 4.0 application program was used for data analysis. The research conducted ten tests and hypotheses, out of which six tests showed a positive effect, while four other tests had no effect. The hypothesis tests were carried out to investigate the influence of brand image variables on buying decisions, quality of service on buying decisions, celebrity endorsers on consumer trust, and celebrity endorser variables on buying decisions through consumer trust. However, The results of the test indicate rejection of the hypothesis, suggesting that no significant effect was found between one variable and another. This research is expected to contribute to the development of knowledge in Marketing Management, especially for scientists interested in analyzing the relationship between celebrity endorsers, brand image, and quality of service on buying decisions through consumer trust.